Isolation and molecular characterization of EgCBF3 encoding oil palm CBF/DREB transcription factor and effects of its ectopic expression in tomato (Solanum lycopersicum L. cv. MT1) - Ebrahimi, Mortaza (2015)
One of the well understood mechanisms in plants to overcome biotic and abiotic stresses is mediated through transcription factors. The APETALA2/Ethylene Response Factor (AP2/ERF) is one of the plant specific transcription factors. They are categorized into three families, termed AP2, RAV and ERF. ERF family is divided into two major subfamilies; the Ethylene Responsive Factors (ERF) and the C repeat-binding factor/dehydration responsive element-binding factor (CBF/DREB). In this study, a new member of the CBF/DREB was isolated from oil palm (Elaeis guineensis var. Dura × Pisifera) ripening fruit and designated as EgCBF3. Bioinformatics analysis revealed that EgCBF3 belongs to A-1 subgroup of CBF/DREB subfamily. The transcripts of EgCBF3 were detected ubiquitously, in oil palm’s root, leave and mesocarp tissue. This gene was responsive to the cold, ethylene, abscisic acid, NaCl and polyethylene glycol treatments. The EgCBF3::mGFP fusion protein was localized to the nucleus of onion epidermal cells. Using in vitro and in vivo DNA-protein binding assays it has been shown that EgCBF3 was able to bind with DRE/CRT element. Expression pattern of polygalacturonase (SlPG) and SlE8 two fruit ripening related genes were affected under transient overexpression of EgCBF3 in tomato fruits at four different developmental stages. Two carotenoid biosynthesis-related genes phytoene desaturase (SlPDS) and phytoene synthetase (SlPSY) showed up regulation at four studied stages. Same result was observed for 9-cis-epoxycarotenoid dioxygenase (SlNCED1). The ethylene biosynthesis related genes demonstrated an expression pattern related to the fruit developmental stages. These results predict that EgCBF3 can mediate abiotic stress response in ripening fruits and regulates the ripening process through modulation of ethylene and abscisic acid biosynthesis. Functional characterization of EgCBF3 was further performed using stable transformation of tomato cv. MT1. An in vitro technique was developed for efficient regeneration of transgenic tomato. Seed pretreatment with Thidiazuron (TDZ, 1 mg/l) enhanced organogenesis of the cotyledonary leaf with abaxial side down on MS medium supplemented with 2 mg/l Benzyl Amino Purine (BAP) and 0.02 mg/l Indole Acetic Acid (IAA). The EgCBF3 tomatoes demonstrated dwarfism for the first few weeks, delayed leaf senescence and flowering time, increased chlorophyll content (~0.085 mg/cm2) and abnormal morphology compare to wild type. In vitro studies of the transgenic lines confirmed that overproduction of EgCBF3 can enhance drought, salt and cold tolerance in tomato. Expression of ethylene biosynthesis-related genes encoding 1-aminocyclopropane-1-carboxylic acid synthase (ACS) and 1-aminocyclopropane-1-carboxylic acid oxydase (ACO) were down-regulated in transgenic lines. Also, the studied pathogenesis-related genes showed altered expression in wounded leaves of transgenic plants compared to wild types. These findings were consistent with the hypothesis that EgCBF3 can modulate plant growth and development, as well plant biotic and abiotic stress tolerance through direct regulation of related regulons, and partly via ethylene regulatory pathway.